Re-purposing Chloroquine for Glioblastoma: Potential Merits and Confounding Variables - Weyerhäuser, Patrick; Kantelhardt, Sven R.; Kim, Ella L. (Frontiers in Oncology, 2018)
There is a growing evidence that antimalarial chloroquine could be re-purposed for cancer treatment. A dozen of clinical trials have been initiated within the past 10 years to test the potential of chloroquine as an adjuvant treatment for therapy–refractory cancers including glioblastoma, one of the most aggressive human cancers. While there is considerable evidence for the efficacy and safety of chloroquine the mechanisms underlying the tumor suppressive actions of this drug remain elusive. Up until recently, inhibition of the late stage of autophagy was thought to be the major mechanism of chloroquine-mediated cancer cells death. However, recent research provided compelling evidence that autophagy-inhibiting activities of chloroquine are dispensable for its ability to suppress tumor cells growth. These unexpected findings necessitate a further elucidation of the molecular mechanisms that are essential for anti-cancer activities of CHQ. This review discusses the versatile actions of chloroquine in cancer cells with particular focus on glioma cells.